Type VII secretion system gene mutations driving global mycobacterium tuberculosis transmission revealed by whole genomic sequence - Yang, Jian-Jun; Hu, Yuan-long; Sun, Ping-yi; Wang, Ling; Xie, Xian-Jin; Wang, Ting-Ting (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPathogenic mycobacteria are able to transfer virulence factors across their complex cell wall using a type VII secretion system (T7SS)/early secreted antigenic target-6 of the kDa secretion system (ESX). Since the discovery of ESX loci during the Mycobacterium tuberculosis H37Rv genome project, extensive research in areas such as structural biology, cell biology, and evolutionary analysis has improved our understanding of the role of these systems. However, regulatory mechanisms for ESX in Mycobacterium tuberculosis remain elusive. Despite extensive research, the effects of ESX gene mutations on the dynamics of Mycobacterium tuberculosis transmission are not well understood. In this study, we investigated the role of ESX mutations in TB transmission, assessing their risk and characteristics. We analyzed 13582 whole genome sequences of Mycobacterium tuberculosis isolates, of which 6130 (45.13%) were clustered strains. Initially, Boruta algorithm was used to pinpoint SNPs that were significant for TB transmission. These SNPs were then subjected to univariate and multivariate logistic regression analysis to determine the significance of each SNP. The intersection of these two independent methods was recognized as the optimal set of risk mutations for TB transmission. Specifically, we identified one risk mutation (espA(Rv3616c, 4055801)) in L1, four risk mutations (espK(Rv3879c, 4357597), esxU(Rv3445c, 3863138), esxO(Rv2346c, 2626018), and esxW(Rv3620c, 4060588)) in L2, and four risk mutations (eccE1(Rv3882c, 4362807), espE(Rv3864, 4340330), espA(Rv3616c, 4055993), and eccC5(Rv1783, 2019942)) in L4. These risk mutations were significantly associated with clustering, potentially increasing TB transmission. Our findings suggest that mutations in ESX genes play a crucial role in Mycobacterium tuberculosis transmission. These results can be applied to the development of novel strategies for the treatment and prevention of disease.